Glutathione-S-transferase A3 protein suppresses thiram-induced tibial dyschondroplasia by regulating prostaglandin-related genes expression. (March 2021) - Niu, S.; Li, X.; Jahejo, A.R.; Zhang, N.; Yang, S.X.; Jia, Y.F.; Zhang, Y.Y.; Tian, Z.X.; Li, Z.; Ning, G.B.; Zhang, D.; Tian, W.X.
Abstract: Tibial dyschondroplasia (TD) is an intractable avian cartilage disease in which proximal growth plates of tibia lack blood vessels and contain nonviable cells, and it leads to the inflammatory response. Prostaglandins (PGs) genes have not been studied yet in TD chicken, and they might play role in skeletal metabolism, therefore we planned to explore the role of recombinant glutathione-S-transferase A3 (rGSTA3) protein and PG-related genes. In this study, qRT-PCR, enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry (IHC) analysis were used to identify the expression patterns of eight PG-related genes in the tibial growth plate of broiler chicken. The results showed that the expression of PG-related genes glutathione-S-transferase A3 (GSTA3), cyclooxygenase 2 (COX-2), prostaglandin D2 synthase (PTGDS), prostaglandin E synthase (PTGES), prostaglandin E2 receptor (PTGER) 3, PTGER4, prostaglandin reductase 1 (PTGR1) and hematopoietic prostaglandin D synthases (HPGDS) expression were identified and could significantly respond to thiram-induced TD chicken. Interestingly, the expression of rate-limiting enzyme COX-2 and PGE2 were induced after the treatment of rGSTA3 protein. These findings demonstrated that the occurrence of TD is closely related to the inhibition of PGs. Moreover, rGSTA3 protein participated in the recovery of TD by strengthening the expression of PG-related genes. Highlights: Chicken tibial growth plate constitutively express 8 types of PG-related genes at the transcript level. Thiram-induced TD is closely connected with the inhibition of PGs. rGSTA3 protein participate in the recovery of TD by regulating the expression of PG-related genes.